State-dependent pricing of monetary policy nonlinearities and inflation at risk for China - Xiao, Q.; Cao, H.; He, Y.; Oxley, Leslie (2025)
As global uncertainty rises and inflationary pressures increase, understanding the transmission mechanisms through which monetary policy affects the economy is crucial for formulating policies that promote economic growth and stabilize inflation. This study specifically focuses on the nonlinear effects of monetary policy on inflation and output. Grounded in state-dependent pricing theory, we employ a smoothed local projection method to analyze the nonlinear responses of macroeconomic variables to monetary policy shocks of different scales and in high and low inflation regimes. Additionally, quantile regression is utilized to measure inflation at risk. Our findings affirm the role of state-dependent pricing in China's monetary policy transmission mechanism. Notably, inflation responds more significantly to price-based monetary policy, whereas output exhibits a stronger reaction to quantity-based monetary policy, particularly in high inflation scenarios. The inflation forecast distribution conditioned on exchange rates indicates that rising inflation levels are associated with increased risks, with higher inflation volatility heightening the upside risks of inflation. This research deepens our understanding of the dynamic monetary policy transmission mechanism in China and provides valuable policy insights for effectively managing inflation and promoting economic growth.